Redesign Model Instalasi Pipa Saluran Air Bersih Di Desa Toniku Jailolo Selatan - Muhammad Muzni Herbelubun; Rudi Hartono; Witono Hardi (Patria Artha Journal of Community (PKM), 2022)
The purpose of the service program to redesign the installation of clean water pipelines is to provide new installations and repair clean water distribution pumps that are able to distribute clean water originating from river water in the Toniku Village area so that the water distribution system runs more evenly, both to the reservoir and to the reservoir. the community directly. The implementation of the activity begins with an initial survey to see the condition of the artificial wells and water reservoirs that will be repaired where there are artificial wells installed on the banks of the river. Repairs to the pipe installation are carried out by replacing 2 4-inch pipes so that the flow of water that will enter the reservoir does not suffer losses or is wasted. The initial design before the change was that there were many pipe connections that were installed from the pump to the reservoir so that the water flowing into the reservoir experienced a lot of loss or wasted a lot. From the results of the field review, the electrical capacity to drive the pump is not sufficient because the type of electrical cable connected is not suitable or unable to drive the two pumps. Errors also occur in the installation of capacitors where the pump has a 40 F capacitor type but the one installed is 50 F. For the problem of electricity capacity, the village government has tried to coordinate with PLN to replace the power cable. As for the capacitor problem, in this program we bought 2 capacitors to be replaced and installed. Keywords: Redesign, Water Pump, Reservoir, Drain Installation